ANALYSIS OF ANTI-BRIBERY PERCEPTIONS ON SEAFARERS’ TRAINING SERVICES IN SEKOLAH TINGGI ILMU PELAYARAN TOWARDS THE CAMPUS WITH THE PREDICATE OF CLEAN AND SERVICE BUREAUCRACY AREA (WBBM) - Retno Sawitri Wulandari; A. Chalid Pasyah (Dinasti International Journal of Education Management And Social Science, 2022)
Sekolah Tinggi Ilmu Pelayaran Jakarta (STIP), a Maritime Higher Education Institute, has a vision to become an International Standard Maritime Education Institution that produces professional Shipping Human Resources. This vision is supported by a commitment to establish, maintain and review anti-bribery policies that put forward the principles of clean, transparent, and accountable governance as an effort towards a Clean and Serving Bureaucracy Area (WBBM). The policy of realizing good institutional governance and assessing commitment to corruption prevention refers to the regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform (Men.PAN & RB ) Number 10 of 2019 concerning amendments to the regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform (Men.PAN & RB ) Number 52 of 2014 concerning Guidelines for the Development of an Integrity Zone Towards a Corruption-Free Area and a Clean Bureaucracy Free Area and Serving in Government Agencies. STIP's anti-bribery performance measurement on service delivery is carried out with a survey that produces the Anti-Corruption Perception Index (IPAK). Service delivery in general is 89.95 classified in category A, so the performance is declared very good. Elements that support the performance of clean, transparent, accountable service delivery, especially free from requests for money for services, brokering practices, and services in return. As for the performance of other services, the formation training and education was obtained by 91.93 obtaining a quality value of A. Meanwhile, skills training services were at 87.11, updating training at 85.89, and skills training at 84.47 obtaining a B quality score.